Prelude No.4 by Heitor Villa Lobos : Classical guitarist awareness of correct interpretation of repertoire / Muhammad Nur Hafif Mohd Khairul Anuwar - Mohd Khairul Anuwar, Muhammad Nur Hafif (2016)
The purpose of this study is to discuss the approaches of interpretation used by students in their performance. To be more in depth, this study aims to investigate the relationship of imagination and expression in delivering performances as well to find out problems faced by students towards delivering expressive musical performances. This research is conducted by interviewing a well-known classical guitarist, Fabio Zanon and by giving questionnaire to students from Faculty of Music UiTM, Shah Alam. The methodology for this full study involves eight (8) questions for interview sessions that were specifically focused on the awareness of correct interpretation of repertoire as well for the right techniques approaches. Besides that, this study give someone to understand on recording by three (3) different performances of the same repertoire will be analysed and discussed regarding its awareness on the repertoire, experiences, knowledge of the characteristic for Brazilian-Indian music, right-hand techniques, problem faced by students in order to replicate the repertoire which is Prelude No.4 by Heitor Villa-Lobos that shows its applied interpretation. Which will be part of the findings in this study.